Bahan Bakar Padat Dari Pelepah Sawit Menggunakan Proses Torefaksi; Variasi Suhu Dan Ukuran Bahan Baku - Susilowati, Susilowati; Helwani, Zuchra; Komalasari, Komalasari (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Oil Palm Frond can be used as alternative energy source by using torrefaction process. Torrefaction is a pre-treatment process of biomass into solid fuel within temperature range of 200-300oC in an inert condition. This research aims to produce solid fuel from oil palm frond and study the effect of process variabel towards characteristic of solid fuel resulted. Torrefaction of empty fruit bunch was using fixed bed horizontal reactor with temperature (250-300oC) and particle size (5-15 mm). Product quality resulted was calorific value, mass yield, energy yield and proximate (moisture content, ash content, volatile content and fixed carbon). The result obtained for calorific value in range was 19513.82-22684.77 kJ/kg, mass yield was 47.93-71.64 %, and energy yield was 65.09-86.39 %. 17091.03-20697.13 kJ/kg, mass yield was 52.63-84.52% and energy yield was 64.12-99.05%. Proximate analysis resulted in the form of moisture content was 1.81-3.25 %, ash content was 4.54-6.13 %, volatile content was 40.95-63.48 %, and fixed carbon was 28.62-51.53. from the result obtained, the effect of rising temperature give enhancement to the calorific value, energy yield, ash content, and fixed carbon. While the influence of increasing particle size give enhancement to the mass yield, calorific value, moisture and volatiles content. From the result of hypothesis testing using F test showed that Fcalculated was greater than Ftable. This indicates that the data obtained significant influence and according to the resulting model.Keywords: biomass, oil palm frond, solid fuel, torrefaction.